A strong convergence of a modified Krasnoselskii‐Mann method for non‐expansive mappings in Hilbert spaces - Yao, Yonghong; Cho, Yeal Je (Mathematical Modelling and Analysis, 2010)
In this paper, we introduce a new method based on the well‐known Krasnoselskii‐Mann’s method for non‐expansive mappings in Hilbert spaces. We show that the proposed method has strong convergence for non‐expansive mappings. Keywords: non‐expansive mapping, fixed point, modified Krasnoselskii‐Mann’s method, strong convergence, Hilbert space. First published online: 09 Jun 2011